Misoprostol teratogenicity in six Filipino children : a case series - Chiong, Mary Anne D.; Cutiongco-de la Paz, Eva Maria
Misoprostol is a prostaglandin analogue that has been misused as an abortifacient. We report on six Filipino children who were exposed to the drug in utero with consequent craniofacial and limb abnormalities. Moebius sequence was seen in three of them, two presented with hydrocephalus and limb reduction defects, and one had the oromandibular limb hypogenesis spectrum of defects.
In: Acta Medica Philippina, 2009 vol 43 (1) pages: 52-56
Keywords: Teratogens; Misoprostol